Pulsed power capacitor design based on 3D inkjet printing - Xinxin Cao; Shixuan Mei; Jinjin Hao; Qikun Jia; Bolin Qin; Zhikuan Xu; Fei Lv; Kuanwei Zhang; Xueli Nan (Electrochemistry Communications)
This paper presents a new method for manufacturing multilayer chip capacitors using three-dimensional inkjet printing technology. Compared with the traditional method of manufacturing multilayer chip capacitors, it enables the design of complex structures without molds. It has the advantages of high integration, integrated printing, and simple operation. In addition, the electrode structure of the conventional capacitor is optimized by replacing the original electrode tip with a ‘circular’ pressure-even electrode structure. The effects of different circle radii on the electric field distribution inside the capacitor were analyzed using Comsol simulation software. The results show that the homogeneous pressure electrode structure proposed in this paper can effectively improve the electric field concentration at the electrode tip of the capacitor. Finally, the capacitor was fabricated using 3D inkjet printing technology, and the capacitance value, voltage withstand value, and other parameters of the capacitor were measured. The capacitor with an even-pressure electrode structure was able to improve the breakdown voltage by about 22 %, which is consistent with the expected experimental results. The possibility of fabricating pulsed power capacitors using 3D inkjet printing technology was confirmed.